2017
DOI: 10.1111/bju.13793
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening practices in a large, integrated health system: 2007–2014

Abstract: Objectives To assess prostate cancer (PCa) screening practices in primary care since the initial United States Preventive Services Task Force (USPSTF) recommendation against prostate specific antigen (PSA) testing for older men, and to assess primary provider variation associated with PCa screening. Patients and Methods Our study population included 160, 211 men age >= 40 with at least 1 visit in a primary care clinic in any of the study years in a large, integrated health system. We conducted a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
25
0
2
Order By: Relevance
“…Regardless of training, the majority (61%) of PCPs in our sample only offered and recommended a PSA test to some patients after taking individual risk and other factors into account rather than routinely screening all men. This behavior is consistent with the recommendations of professional organizations (Qaseem et al, 2013; American Urological Association) against routine screening for prostate cancer for all men, mirrors the overall decline in use of the PSA test by PCPs since 2000 (Schmidt, 2017; Misra-Hebert et al, 2017), and acknowledges PCP consideration of individual patient factors as well as patient preferences and values that may influence each screening decision. Some PCPs continue to routinely screen asymptomatic men for prostate cancer, but the majority appear to practice more in line with the 2012 recommendation.…”
Section: Discussionsupporting
confidence: 73%
“…Regardless of training, the majority (61%) of PCPs in our sample only offered and recommended a PSA test to some patients after taking individual risk and other factors into account rather than routinely screening all men. This behavior is consistent with the recommendations of professional organizations (Qaseem et al, 2013; American Urological Association) against routine screening for prostate cancer for all men, mirrors the overall decline in use of the PSA test by PCPs since 2000 (Schmidt, 2017; Misra-Hebert et al, 2017), and acknowledges PCP consideration of individual patient factors as well as patient preferences and values that may influence each screening decision. Some PCPs continue to routinely screen asymptomatic men for prostate cancer, but the majority appear to practice more in line with the 2012 recommendation.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, one study conducted in a group of primary care clinics concluded that the USPSTF guideline was not followed in such a way that the no-screening message was brought equally to all men; men with a family history were more likely and African American men less likely to be screened, and older men received a more balanced counselling on PSA testing. 38 …”
Section: Resultsmentioning
confidence: 99%
“…One of the implications of the category ‘D’ assigned to PSA screening by the USPSTF guidelines was a substantial universal decline in PSA screening across all age groups . This trend in decreased PSA screening across all age groups has indeed been the case in Australia as well .…”
Section: Discussionmentioning
confidence: 99%